The beginning of image development by the society in the interpretation of A.S. Pushkin's works during his lifetime - D.V. Tumanov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The genesis of the mythologization of the biography and creative heritage of A.S. Pushkin has been discussed. Social imagery is the area of synthesis in the public consciousness of literary reputation and literary myth. The stages of its formation in the lifetime criticism and memoirs of A.S. Pushkin’s circle have been considered. It has been emphasized that the creativity and personality of the poet became for the first time of interest at the early stage of his development: the first attempt to form the literary reputation of the poet influenced not only the vector of subsequent analysis of his works, but also the trajectory of his creative work. With the active participation of the writer, his literary reputation merged with the literary myth about him. The paper shows how this construct developed as a result of the conceptual integration of the temporal experience into the spatial-visual images, semantic frames and narratives.